Unformatted text preview: i )n−1 + B (1 + i )n−2 + … + B Subtract equation (2) from equation (1): (1) − (2) F − F (1 + i )−1 = B [(1 + i )n − 1] Multiply both sides by (1 + i): F (1 + i ) − F = B [(1 + i )n+1 − (1 + i)] So the equation is: F = B[(1 + i )n+1 − (1 + i)]/i Applied to the numerical values: F = 100/0.08 [(1 + 0.08)7 − (1.08)] = $792.28 440 (a) (b) S = $50 ( P/G , 10%, 4) = $50 (4.378) = $218.90 (c) T = $30 ( A/G , 10%, 5) = $30 (1.810) = $54.30 448 P = $100 (P/A, 10%, 4) + $100 (P/G, 10%, 4) = $100 (3.170 + 4.378) = $754.80 Also: P = 4B (P/A, 10%, 4) − B (P/G, 10%, 4) Thus, 4B (3.170) − B (4.378) = $754.80 B = $754.80/8.30 = $90.94...
View
Full Document
 Spring '11
 Kashayar
 Nominal Interest Rate, unpaid balance, P/A, Subtract equation

Click to edit the document details